Experimental Study of Geometrical Accuracy of Artec Leo 3D Scanner on Complex Object Scanning (Jurnal Vokasi Mekanika, 2025)
This study aims to measure the geometrical accuracy of complex object scanning using the Artec Leo 3D scanner. The scanned object is a wheel rim, with eight combinations of parameters including variations in distance (50 cm and 100 cm), scanning angle (45° and 90°), and lighting conditions (indoor and outdoor). Deviations were measured from four reference points on the scanned model and compared to a reference model. The results show that the Indoor configuration with a scanning distance of 50 cm and a scanning angle of 90° gives the smallest deviation of 0.025 mm (0.01%), while the Outdoor configuration with a scanning distance of 50 cm and a scanning angle of 45° produces the largest deviation of -3.275 mm (-1.80%). The overall average deviation of all combinations is -0.63 mm or -0.36%, indicating that the Artec Leo can produce high accuracy if configured with the right parameters. The smallest deviation was obtained under indoor scanning conditions with a scanning distance of 50 cm and a scanning angle of 90°.